2022
DOI: 10.3390/agronomy13010072
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming of Rice Varieties with Decoyinine Improve Their Resistance against the Brown Planthopper Nilaparvata lugens

Abstract: The brown planthopper (BPH), Nilaparvata lugens Stål (Hemiptera: Delphacidae) is one of the most destructive rice pests in Asia. The microbial metabolite decoyinine (DCY) has been extracted from Streptomyces hygroscopicus. Recent studies have suggested that treating rice seeds with DCY could improve the growth and yield of rice. To further assess the effects of priming the seeds of different rice varieties with DCY on rice seedling resistance against BPH, an age-stage, two-sex life table and choice test were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Recently, a growing body of evidence has suggested that GV also fortifies plants against pest damage (Figure ). Priming rice seeds with GV has been found to enhance resistance to brown planthopper (BPH, Nilaparvata lugens) and small brown planthopper (SBPH, Laodelphax striatellus) by significantly reducing their fertility. Physio-biochemical analyses indicate that when GV-treated rice was fed upon by BPH, there was an enhancement in the activities of plant defense-related enzymes including superoxide dismutase (SOD), catalase (CAT), glutathione S transferase (GST), peroxidase (POD), and polyphenol oxidase (PPO) . Additionally, transcriptomic analyses showed that these feeding events precede the upregulation of 15 resistance-related WRKY genes.…”
Section: Effect Of Guvermectin On Plant Biotic and Abiotic Stressesmentioning
confidence: 99%
“…Recently, a growing body of evidence has suggested that GV also fortifies plants against pest damage (Figure ). Priming rice seeds with GV has been found to enhance resistance to brown planthopper (BPH, Nilaparvata lugens) and small brown planthopper (SBPH, Laodelphax striatellus) by significantly reducing their fertility. Physio-biochemical analyses indicate that when GV-treated rice was fed upon by BPH, there was an enhancement in the activities of plant defense-related enzymes including superoxide dismutase (SOD), catalase (CAT), glutathione S transferase (GST), peroxidase (POD), and polyphenol oxidase (PPO) . Additionally, transcriptomic analyses showed that these feeding events precede the upregulation of 15 resistance-related WRKY genes.…”
Section: Effect Of Guvermectin On Plant Biotic and Abiotic Stressesmentioning
confidence: 99%
“…BPH strain was reared on TN1 plants in a chamber (27 ± 1 °C, relative humidity of 70 ± 5%, and a photoperiod of 16 h:8 h (L:D)). 42 2.2 The cultivation and inoculation of P. indica P. indica strain was provided by Jiangsu Lixiahe District Institute of Agricultural Sciences. P. indica stored at −80 °C was inoculated on the plate medium of potato dextrose agar (PDA) and cultured at 28 °C for 7 days, and then inoculated into the potato dextrose broth (PDB) liquid medium at 28 °C for 7 days at 180 rpm on an incubator shaker.…”
Section: Plant Materials and Insectsmentioning
confidence: 99%
“…After laying, rice seedlings were replaced every 3 days, and the numbers of laid eggs were counted until the female adult died. 42…”
Section: Development and Reproduction Of Bphmentioning
confidence: 99%
See 1 more Smart Citation